Toward understanding the convergence of researcher and stakeholder perspectives related to water-energy-food (WEF) challenges: The case of San Antonio, Texas. Issue 104 (February 2020) - Daher, Bassel; Hannibal, Bryce; Mohtar, Rabi H.; Portney, Kent
Highlights: Importance of "spot-checking" convergence between researchers and stakeholders Aspects of convergence between researchers and regional stakeholders over issues of WEF Modest levels of communication between respondents and WEF organizations Convergence on the high potential of information sharing and improved communication Abstract: In the past decade, research on interconnected resource challenges has primarily focused on quantifying physical resource interconnections, and there is a growing focus on the social, economic, and policy dimensions of these interconnections. While the nature of the complexity of interconnected resource challenges resulted in emphasizing the need for inter- and trans-disciplinary research and in increased collaboration between research groups, little work has examined the convergence of perspectives between the research groups and their respective stakeholders. This paper focuses on the San Antonio Region of Texas: a resource hotspot characterized by rapid urbanization, increased energy production in the Eagle Ford Shale Play, and growing agricultural activity. The paper reports on a survey sent to 370 researchers and regional stakeholders from governmental, non-governmental/non-profit, and business organizations in the Region's water, energy, or food sectors. The study goals were to 1) evaluate levels of convergence in perspectives regarding the water, energy, and food challenges in the Region; 2) quantify existing levels of communication of both researchers and regional stakeholders with identified WEF organizations in the region; and 3)identify barriers to and opportunities for improving communication between the WEF organizations and the researchers involved. The authors found aspects of convergence between surveyed regional stakeholders and researchers. Aspects of convergence exist between both groups regarding the potential of different Texas Development Water Board strategies to address future water challenges. Modest levels of communication were reported between surveyed researchers and regional stakeholders with other identified WEF organizations. Both groups converge on the potential roles of "increased communication" and "sharing information between agencies" as a means to improve cooperation to address interconnected resource challenges. To make this possible, institutional mechanisms and resource allocations for such activities must be revisited.